Infections and risk of epilepsy in children and young adults: A nationwide study. (21st December 2018) - Ahlers, Frederik S.; Benros, Michael E.; Dreier, Julie W.; Christensen, Jakob
Summary: Objective: The development of epilepsy has been linked to infections of the central nervous system, but recently also to infections and inflammation outside of the central nervous system. Thus we investigated the association between infections and the risk of subsequent epilepsy. Methods: This was a Danish nationwide population‐based cohort study comprising a total of 1 938 555 individuals born between 1982 and 2012. Individuals were followed from birth until December 31, 2012, death, disappearance, emigration, or epilepsy diagnosis, whichever came first (28 512 666 person‐years of follow‐up). The exposure was hospital contacts for infection and the outcome was a diagnosis of epilepsy as recorded in the Danish National Hospital Register. Hazard ratios were calculated using Cox proportional hazards models adjusted for age, sex, calendar period, Apgar score, gestational age, birth weight, and parental history of epilepsy. Results: A total of 25 825 individuals received an epilepsy diagnosis during the study period, among whom 8235 (32%) had a previous hospital contact for infection. A hospital contact for infection was associated with a 78% increase in the risk of subsequently receiving an epilepsy diagnosis (hazard ratio 1.78, 95% confidence interval [CI] 1.73‐1.83) compared with those without infection. The highest risk was observed after central nervous system infections (hazard ratio 4.97, 95% CI 4.42‐5.59), but increased risks were identified across all infected organ systems and types of pathogens. The risk of receiving an epilepsy diagnosis was correlated with the temporal proximity of the infection ( P < 0.001) and increased with the number of hospital contacts for infection ( P < 0.001) and with the severity of infection ( P < 0.001). Significance: The risk of receiving an epilepsy diagnosis was increased after a wide range of infections, suggesting that systemic inflammatory processes may be involved in the development of epilepsy.